Determination of selenite and selenomethionine in kefir grains by reversed-phase high-performance liquid chromatography-inductively coupled plasma-optical emission spectrometry - Bodur, Suleyman; Oner, Miray; Erarpat, Sezin; Bakirdere, Sezgin (WILEY-V C H VERLAG GMBH, 2021)
A new and efficient reversed-phase high-performance liquid chromatography-inductively coupled plasma-optical emission spectrometry method was developed for the simultaneous separation and determination of SeO32- and seleno-dl-methionine in kefir grains. For the system, limits of detection and quantitation values for SeO32- and seleno-dl-methionine were calculated as 0.52/1.73 mg/kg (as Se) and 0.26/0.87 mg/kg (as Se), respectively. After performing the system analytical performance, recovery experiment was done for kefir grains and percent recovery results for SeO32- and seleno-dl-methionine were calculated as 98.4 +/- 0.8% and 93.6 +/- 1.0%, respectively. It followed by the feeding studies that the kefir grains were exposed to three different concentrations of SeO32- (20, 30, and 50 mg/kg) for approximately 4 days at room temperature to investigate the conversion/non-conversion of SeO32- to seleno-dl-methionine. Next, the fed grains were extracted with tetramethylammonium hydroxide pentahydrate solution (20%, w/w) and then sent to the developed system. There was no detectable seleno-dl-methionine found in fed kefir grains at different concentrations of SeO32- while inorganic or elemental selenium in the fed kefir grains was determined between 1579.5 - 3116.0 mg/kg (as Se). Selenium species in the kefir grains samples was found in the form of SeO32- proved by using an anion exchange column.
Keywords: hyphenated technique; kefir grains; selenite; seleno-dl-methionine; speciation; INORGANIC SELENIUM; ELEMENTAL SELENIUM; MASS-SPECTROMETRY; SAMPLE PREPARATION; ISOTOPE-DILUTION; ENRICHED YEAST; PRECONCENTRATION; MICROEXTRACTION; SELENOCYSTEINE; Chemistry